2011
DOI: 10.3389/fnene.2011.00002
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Effectively Covers Energy Demands during Neuronal Network Activity in Neonatal Hippocampal Slices

Abstract: Although numerous experimental data indicate that lactate is efficiently used for energy by the mature brain, the direct measurements of energy metabolism parameters during neuronal network activity in early postnatal development have not been performed. Therefore, the role of lactate in the energy metabolism of neurons at this age remains unclear. In this study, we monitored field potentials and contents of oxygen and NAD(P)H in correlation with oxidative metabolism during intense network activity in the CA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 58 publications
7
70
1
Order By: Relevance
“…However, the fact that no differences were observed in Up state amplitude, a parameter affected by the level of passive supply of oxygen [41, 55], suggests a similar metabolic demand and supply in slices of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that no differences were observed in Up state amplitude, a parameter affected by the level of passive supply of oxygen [41, 55], suggests a similar metabolic demand and supply in slices of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that in both neonatal and adult slices, supplementing glucose in ACSF with pyruvate or lactate improves synaptic function. 18,37 In vivo, the interstitial fluid in neocortex and hippocampus contains B1 to 2 mmol/L of basal glucose and similar concentrations of lactate (for review, Zilberter et al 38 ), and therefore cells are potentially able to utilize a combination of both substrates. It is also possible that in vivo, under specific physiologic conditions, the neuronal metabolism may be shifted toward lactate utilization.…”
Section: Astrocyte-released Lactate Is Unlikely a Preferred Neuronal mentioning
confidence: 99%
“…In the context of acclimation to cold stress, lactate may represent an important metabolite to support energy metabolism in fish brain. Ivanov and colleagues [70] demonstrated that lactate is an efficient energy substrate to fuel brain aerobic energy metabolism in case of insufficient glucose supply under intense synaptic activity. In this example LDH1 converts lactate to pyruvate and generates cellular NADH pools which represent an important physiological response to neural activation.…”
Section: Discussionmentioning
confidence: 99%